The Courtesan Project and the Tawa'ifs' Cultural Commons. Issue 1 (16th June 2021) - Chanda, Sohini; Patnaik, Archana; Chatterjee, Suhita Chopra
The tawa'ifs were an elite class of performing community engaged in the production of dance, music, and poetry in the form of cultural commons in pre-colonial Lucknow and other princely states. There was a gradual decline in this community's cultural commons throughout the 19th and 20th century. While the performance history of tawa'ifs and their contribution to the art forms of kathak and thumri have been widely explored, there is a sparse understanding of the community's cultural production process, why it was hampered, and if any steps are being undertaken to preserve their cultural resources. Hence, this paper's first objective is to understand the factors that affected the tawa'if community's production of cultural commons. The second objective is to critically analyse a neo-revival project (Courtesan Project) by the Non-Governmental Organization, Sufi Kathak Foundation, and its efforts to re-link kathak and its associated music repertoire with the performing community of tawa'ifs. The arguments will address the gap of academic research on cultural commons produced by tawa'ifs and highlight the neo-revival project's efforts to recreate and reconnect the tawa'ifs' idiosyncratic arts with its community identity. The paper uses cultural commons theory to understand tawa'ifs' production of cultural commons and argues that the loss of desirable community identity, which results in a degraded social value of the community, can lead to a potential social dilemma for the production and maintenance of cultural commons. It further proposes that the Courtesan Project can produce new cultural commons if a community of members with similar interests evolve around its practices.